A high-throughput genetic screening protocol to measure lipid bilayer stress-induced unfolded protein response in Saccharomyces cerevisiae - Ho, Nurulain (2023)
The endoplasmic reticulum (ER) stress is defined by the accumulation of unfolded proteins at the ER and perturbation at the ER membrane, known as lipid bilayer stress (LBS). In turn, ER stress triggers the unfolded protein response (UPR) to restore ER homeostasis. Here, we provide a modified protocol based on the synthetic genetic array analysis in Saccharomyces cerevisiae to identify genetic perturbations that induce the UPR by LBS. This method is adaptable to other canonical stress pathways. For complete details on the use and execution of this protocol, please refer to Ho et al. (2020), Jonikas et al. (2009) and Baryshnikova et al. (2010).